Kumbang Pupus Pisang: Hama Baru? - Dwinardi Apriyanto; Ishak Manti (Universitas Gadjah Mada, 2006)
Many insects have been reported as pests of banana, among which the corm borer (Cosmopolites sordidus Germar) and pseudo-stem borer (Odoiphorus longicollis [Oliver]) are considered as the most important species. We found a beetle species during 2003 pest survey of banana in Rejang Lebong, Bengkulu, that had not been reported before in any publication. The adult feeds on and damages whorl of banana, and therefore we named it as